2007
DOI: 10.1007/s00268-006-0693-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Parathyroidectomy in Patients with End‐stage Renal Disease and Severe Hyperparathyroidism

Abstract: The risk of death of patients with severe SHPT leading to PTX differed from that of nonoperated subjects. The apparent differences in survival may be related to the number and severity of associated comorbidities. ESRD patients who undergo PTX may represent a subset of healthier subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
1
46
0
1
Order By: Relevance
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…KDIGO guidelines currently state that patients with CKD stages 3-5D with severe hyperparathyroidism who fail to respond to medical therapy should undergo parathyroidectomy. This recommendation may have been based on observational, not-randomized clinical trial evidence describing potentially beneficial effects on short-term laboratory parameters and/or on longer-term clinical outcomes including fracture and death (5,6). Some (7)(8)(9)(10)(11)(12) but not all (5) reports suggest that short-term adverse outcomes related to parathyroidectomy produce only modest adverse consequences.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that short-term mortality in end-stage renal dialysis (ESRD) patients was higher following parathyroidectomy, although long-term mortality was lower [20]. Mortality may be increased in those who are older and/or have more comorbidities [21]. …”
Section: Introductionmentioning
confidence: 99%